Article 7. Money, money, money. (Where does it come from, how do we control it, and how far should we go to get more?). Issue 2 (1st March 2002) - Wardrope, J; McCormick, S
Abstract : This is the seventh article in a series on management within the emergency department. This article focuses on financial aspects, including budgets and funding.